2017
DOI: 10.2494/photopolymer.30.605
|View full text |Cite
|
Sign up to set email alerts
|

New Organic Photo-Curable Nanoimprint Resist ≪mr-NIL210≫ for High Volume Fabrication Applying Soft PDMS-Based Stamps

Abstract: Herein, we report on a newly developed and commercialized organic photo-curable Nanoimprint Lithography (NIL) resist, namely mr-NIL210. Since this new NIL resist follows an innovative design concept and contains solely specific monomers with a characteristic chemistry and molecular design, an extended longevity of applied polydimethyl siloxane (PDMS) stamps is enabled addressing a crucial key metric for industrial high-volume manufacturing processes. Moreover, the mr-NIL210 is characterized by a negligible oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The pattern height was over 500 nm from the sixth imprinting cycle. Messerschmidt et al [16] reported that a rectangle pattern was obtained using the same soft UV-PDMS mold and organic UV-curable resin with low viscosity (~50 cP) nanoimprinted with only capillary filling (pressure free) in a standard mask aligner. In this study, we used an inorganic/organic hybrid polymer with medium viscosity (~1500 cP) as the imprint material and the mechanical imprint pressure was 0.1 MPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern height was over 500 nm from the sixth imprinting cycle. Messerschmidt et al [16] reported that a rectangle pattern was obtained using the same soft UV-PDMS mold and organic UV-curable resin with low viscosity (~50 cP) nanoimprinted with only capillary filling (pressure free) in a standard mask aligner. In this study, we used an inorganic/organic hybrid polymer with medium viscosity (~1500 cP) as the imprint material and the mechanical imprint pressure was 0.1 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Soft UV-curable PDMS (UV-PDMS) has the advantage of simple mold replication by UV curing at room temperature, which leads to low film shrinkage. Messerschmidt et al [16] demonstrated 30 consecutive imprinting cycles without any defects using soft UV-PDMS and organic UVcurable resin with low viscosity (~50 cP).…”
Section: Introductionmentioning
confidence: 99%
“…The substrates were cleaned in acetone and IPA for about 10 min each, and then a short oxygen plasma treatment for 10 min was applied in order to obtain the hydrophilic surface. The mr-NIL210 resist [ 54 ] at two standardized versions—200 and 500 nm—was used after prior deposition of an adhesion layer mr-APS1 (acquired both from micro resist technology GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…NIL was initially used as a purely lithographic method, for pattern transfer [ 10 ] as a fast and cheap alternative to electron beam lithography. In recent years, a new trend has emerged towards direct patterning of functional materials, where the imprinted structures are directly used as active elements in devices.…”
Section: Introductionmentioning
confidence: 99%